1261. Utility of a Multiplex Molecular Gastrointestinal Panel in Rapid Identification and Control of a Norovirus Outbreak in a Pediatric Tertiary Care Center. (26th November 2018) - Comeau, Jeannette L; Ivany, Allana M; Romeo, Terry; Maxwell, Bridget S; Nymark, Natalie; MacKinnon, Belinda; Doon, Erin; Mailman, Tim
Abstract: Background: Norovirus is one of the most common viral pathogens implicated in gastroenteritis outbreaks in community and healthcare settings. The virus' short incubation period and high attack rate allow its rapid spread through inpatient wards to patients (Patients), staff and visitors. Early identification and appropriate implementation of infection prevention and control measures is essential to interrupt transmission. Methods: The IWK Health Centre is a 250-bed tertiary care Pediatric and Women's hospital serving the Maritime Provinces, Canada. We describe a norovirus outbreak in our Pediatric Medical Unit, a 24-bed, single room ward with individual bathrooms for patients and families. Hospital-acquired norovirus definition: Patients admitted ≥48 hours with lab-confirmed norovirus AND ≥ 1 of: (1) acute onset diarrhea (no noninfectious cause) or (2) ≥2 of: nausea, vomiting, abdominal pain, fever, or headache. In 2017 the FilmArray Gastrointestinal (GI) Panel was introduced in the Clinical Microbiology Laboratory as part of a prospective post-implementation study. Since then, stool samples sent for viral, bacterial, or parasitic testing are evaluated by PCR. The panel tests for 22 GI analytes, including five viruses, with a 2-hour turnaround time. Previously, in-house stool viral testing was limited to adeno- and rotavirus antigen. Patient characteristics were collected and analyzed for this study. Results: Patients 1, 2, and 3 had new onset diarrhea and emesis; Pt 1 on day 0, and Patients 2 and 3 on day 1. Patient 3's parents (likely source) had had diarrhea and emesis on days 3 and 2, and used the ward kitchen. Two care-givers of Patient 2, and 1 medical resident developed diarrhea and emesis over days 0 to 2. The outbreak was declared over on day 7. Patients 1, 2, and 3 all tested positive for norovirus in stool on day 1. On days 2–3, six other patients with diarrhea tested norovirus negative. All symptomatic patients were immediately placed on contact precautions, room/ward cleaning frequency increased and proper hand hygiene was reinforced. Common areas (playroom/kitchen) were closed until the outbreak was over. All patients with loose stool were tested during the outbreak. Conclusion: FilmArrayGI panel enabled same-day identification of norovirus in this single-ward outbreak and permitted real-time identification of the termination of the outbreak. Disclosures: All authors: No reported disclosures.